2007
DOI: 10.1029/2007gl029679
|View full text |Cite
|
Sign up to set email alerts
|

Highly resolved observations and simulations of the ocean response to a hurricane

Abstract: An autonomous, profiling float called EM‐APEX was developed to provide a quantitative and comprehensive description of the ocean side of hurricane‐ocean interaction. EM‐APEX measures temperature, salinity and pressure to CTD quality and relative horizontal velocity with an electric field sensor. Three prototype floats were air‐deployed into the upper ocean ahead of Hurricane Frances (2004). All worked properly and returned a highly resolved description of the upper ocean response to a category 4 hurricane. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 10 publications
(27 reference statements)
9
141
1
Order By: Relevance
“…Th is is the approximate location relative to the track where the largest near-inertial currents are forced (e.g. Sanford et al, 2007). These profiles are calculated during model runs by inserting synthetic moorings at these two locations with instruments deployed at 5 m vertical intervals.…”
Section: A Results From the Control Experimentsmentioning
confidence: 99%
“…Th is is the approximate location relative to the track where the largest near-inertial currents are forced (e.g. Sanford et al, 2007). These profiles are calculated during model runs by inserting synthetic moorings at these two locations with instruments deployed at 5 m vertical intervals.…”
Section: A Results From the Control Experimentsmentioning
confidence: 99%
“…It has previously been reported that TC-induced sea surface cooling is mainly caused by Ekman upwelling and vertical turbulent mixing (Price 1981;Wada et al 2009a;Sanford et al 2011). The rate of entrainment at the base of the mixed layer caused by the passage of a TC is primarily determined by different horizontal current speeds at different depths across the base (Price 1981;Sanford et al 2007). Wada et al (2010) suggested that vertical turbulent mixing caused by breaking surface waves caused by a TC also plays an important role in sea surface cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical ocean model is the three-dimensional and time-dependent Price-WellerPinkel model (3DPWP) as described in Price et al [1994], [see also Price et al [1986], Sanford et al [2007], Sanford et al [2011]]. The model uses the three-dimensional primitive equations given in equations 1-3 and hydrostatic model to simulate the upper ocean response to a hurricane.…”
Section: Description Of Modelmentioning
confidence: 99%